2021
DOI: 10.3390/molecules26154442
|View full text |Cite
|
Sign up to set email alerts
|

Kabuli and Apulian black Chickpea Milling By-Products as Innovative Ingredients to Provide High Levels of Dietary Fibre and Bioactive Compounds in Gluten-Free Fresh Pasta

Abstract: Gluten-free (GF) products, including pasta, are often characterised by nutritional deficiencies, such as scarce dietary fibre and excess of calories. Chickpea flour is increasingly being used by the food industries. Hulls, rich in dietary fibre and bioactive compounds, are discarded after milling. The aim of this work was to evaluate the quality features of short-cut GF fresh pasta added of hull (8% w/w) derived from kabuli (KH) or Apulian black (ABH) chickpeas, in comparison with control GF pasta prepared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
(77 reference statements)
2
7
0
Order By: Relevance
“…Regarding protein content, the maximum levels were observed in the samples containing black and germinated chickpea flours (Table 2). In accordance with this result, Costantini et al 31 . reported that protein amount of pasta enriched with black chickpea hull was higher than pasta enriched with regular chickpea hull.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Regarding protein content, the maximum levels were observed in the samples containing black and germinated chickpea flours (Table 2). In accordance with this result, Costantini et al 31 . reported that protein amount of pasta enriched with black chickpea hull was higher than pasta enriched with regular chickpea hull.…”
Section: Resultssupporting
confidence: 63%
“…Regarding protein content, the maximum levels were observed in the samples containing black and germinated chickpea flours (Table 2). In accordance with this result, Costantini et al 31 reported that protein amount of pasta enriched with black chickpea hull was higher than pasta enriched with regular chickpea hull. Compared to bread prepared with mature chickpea flour, the addition of fermented chickpea flour slightly reduced protein amount of bread (Table 2), potentially because of the lower protein level of fermented chickpea flour (Table 1).…”
Section: Chemical Composition Of Loavessupporting
confidence: 58%
“…In recent years, numerous studies have focused on the innovative food applications of legumes. Legume-based dairy-free cheese alternatives, as well as burgers, salad dressings, pasta, and bakery products have been proposed [10,[13][14][15][16][17][18]. Moreover, pregelatinized legume flours, prepared by means of extrusion-cooking, show hydrocolloid properties, making them suitable for the formulation of GF baked goods [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This Apulian black type has a valuable nutritional composition, characterized by a high content of proteins, polyunsaturated fatty acids and antioxidants such as anthocyanins and carotenoids [ 14 , 15 , 16 ]. To limit the risk of genetic erosion of this valuable chickpea species, trials to formulate foods, such as pasta, bakery goods and puree containing Apulian Black chickpea flours, were successfully performed [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%